"Inequality in Work Time: Gender and Class Stratify Hours and Schedules, Flexibility, and Unpredictability in Jobs and Families". Issue 12 (2nd December 2015) - Gerstel, Naomi; Clawson, Dan
Abstract: Work time is deeply stratified by gender and class. In this review, we first summarize the research discussing the number of hours that people work, the scheduling or timing of those hours as well as the flexibility and unpredictability of work time, discussing the ways all three are stratified. Second, we examine research on the ways work time is mandated, negotiated and contested. This part focuses on the processes, institutions and relations that explain inequality in hours and schedules—beginning with a discussion of relations at the work place, then turning to relations outside the workplace, especially family dynamics, and finally examining policies and politics about work time.